Core-shell structure Co–Ni@Fe–Cu doped MOF–GR composites for water splitting. (26th April 2021) - Fu, Mingxuan; Ning, Guyang; Liu, Jiaxian; Zhang, Qi; Sun, Yuena; Fan, Xinyu; Wang, Haiyang; Lu, Haijun; Zhang, Yufan; Wang, Huan
Abstract: What is essential to solving energy scarcity problems is that develop the high activity, durable and non-noble metal-based dual-functional electrocatalysts for hydrogen evolution reactions (HER) and oxygen evolution reactions (OER). In this work, a series of core-shell structure M@Fe–Cu-GR nanocubes (NCs) are prepared. In the prepared process, the bimetallic FeCu prussian blue analogues (PBA) is used as precursor, transition metals ions Co 2+ and Ni 2+ are introduced into the FeCu-PBA using the exchange of potassium ions with other metal ions, and then the FeCu-PBA are successfully loaded on the graphene oxide (GO) employed the attraction of opposite charges between polydiallyldimethylammonium chloride (PDDA) and GO. Electrochemical tests show that the Tafel slope of Co–Ni@Fe–Cu–GR NCs for HER and OER are 60 and 82 mV dec −1, respectively, and Co–Ni@Fe–Cu–GR NCs shows excellent performance in long-term stability test. Highlights: Core-shell structure M@Fe–Cu–GR nanocubes (M = Co, Ni) were prepared. Introduction the metals into the PBA by the exchange of potassium-tannic acid. The opposite charge attraction was employed to anchor MOFs on the GO. The formation of core-shell structure and graphene were realized in one step. High electrocatalytic performance for both HER and OER.